Modelagem da distribuição de diâmetros em povoamentos de paricá sob diferentes espaçamentos - Aragão, Mariana de Aquino (2018)
Knowledge about tree growth and forest products, as well as estimates of these variables, are essential to enable the planning, management and control of a forest. The modeling of the diameter distribution is widely used for this purpose, it also allows a current description of the forest stand, allows the production projection and aid in the decision making. Thus, this work aims to propose a system of projection of the diameter distribution for Schizolobium parahyba var. amazonicum (Huber ex Ducke) Barneby (paricá) stands under different spacings. The data used in this research came from homogeneous stands of the paricá, located in the state of Pará, arranged under the spacings 3x2, 3x3, 3x4, 4x4 and 5x5 m. The functions Weibull 2 and 3 parameters, Weibull 2 parameters with location parameter fixed in the minimum DBH, Weibull 3 parameters truncated to the right, Hyperbolic 2 and 3 parameters, Log-logistic 2 and 3 parameters and Logistics-generalized were fitted. to stands of Schizolobium parahyba var. amazonicum. After the fit of the pdf's, the Kolmogorov-Smirnov test was applied for the evaluation of adherence to the data, at 5% of significance, as well as the graphical analysis of the observed and estimated data. The evaluated functions obtained adherence to the data observed above 98%, and according to graphic analysis, the field data were efficiently described in the five spacings studied, indicating that all can be used to model the diameters distribution of the paricá. In the projection of the diameters, the Weibull function was used for the recovery of the parameters because this function is considered more flexible and easy to use. Seven regression models were fitted for each of the spacings. The models were evaluated by means of the determination coefficient ( 2 R ), the bias (B%) and the root mean square error (RMSE%). The shape parameter did not present a good estimate for all spacings, especially for spacings 3x4 and 5x5 m It was possible to obtain systems of equations for the projection of the functions parameters in four of the studied spacings, except for the spacing 5x5 m.